1993
DOI: 10.1002/macp.1993.021940910
|View full text |Cite
|
Sign up to set email alerts
|

Side‐Chain liquid‐crystalline polymers containing a siloxane spacer, 2. Effects of mesogenic groups on the thermal properties of side‐chain liquid‐crystalline polymers containing a disiloxane unit in the spacer

Abstract: A series of side-chain liquid-crystalline polymers was prepared containing disiloxane units in the spacer. The polymers consist of a polymethacrylate backbone and several kinds of mesogenic side groups. For the synthesis of the desired monomers, silanol compounds carrying a mesogenic group were prepared as the intermediates. The polymers were obtained by ordinary free-radical polymerization. As the mesogenic groups, linear-type p-or p'-substituted phenyl and biphenylyl benzoates, p-or m-substituted benzoyloxyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…3 The spacer length of the monomers 3a-3d is almost equal to that of the monomers 7a-7d, which is about 14A. However, it was found that, in the hydrosilylation of ethoxydimethylsilane with allyloxy compounds having the same laterally attached mesogens as 10a and 10b, side reactions mainly occurred to afford the desired product in very low yields, whereupon the silyl group was eliminated in the major products.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…3 The spacer length of the monomers 3a-3d is almost equal to that of the monomers 7a-7d, which is about 14A. However, it was found that, in the hydrosilylation of ethoxydimethylsilane with allyloxy compounds having the same laterally attached mesogens as 10a and 10b, side reactions mainly occurred to afford the desired product in very low yields, whereupon the silyl group was eliminated in the major products.…”
Section: Resultsmentioning
confidence: 97%
“…synthetic procedures of the monomers with a siloxane spacer, 7a-7d, 12a, and 12b, have been already described in our previous report. 3 Details of the preparations of the monomers, 3a-3d, including those of their intermediates are described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…action of sodium hydroxide, followed by the eseri® cation In the above reaction, 4-cyano-4¾ -hydroxybiphenyl of 6 a± 6 c with 4-cyanophenol or 4-cyano-4¾ -hydroxywas used instead of 4-cyanophenol to a ord M -7 ( yield: biphenyl to a ord the mesogenic ole® n compounds 71 per cent). moiety would prevent the liquid crystalline order of the mesogenic side chains [4].…”
Section: Synthesis Of Monomers (M -6± M -7)mentioning
confidence: 99%
“…The introduction of a siloxane bond in the spacer (siloxane spacer) a ected the phase transition behaviour and especially decreased the glass transition temperature (T g ) of the obtained polymers. As a result, the mesophase of SCLCPs containing a siloxane spacer appeared at the lower temperature range than that of SCLCPs containing an alkylene spacer with the same backbone components and mesogens [4,6 ]. In our Scheme In this paper, the convenient synthetic route of P-1± P-6 were carried out under an argon stream at the scanning rate of Ô 10ß C min Õ 1 , and those of P7 were monomers of SCLCPs containing siloxane spacers is presented.…”
Section: Introductionmentioning
confidence: 95%